The Role of Ubiquitin-Proteasome Pathway and Autophagy-Lysosome Pathway in Cerebral Ischemia. (1st February 2020) - Chen, Chunli; Qin, Haiyun; Tan, Jieqiong; Hu, Zhiping; Zeng, Liuwang
Abstract : The ubiquitin-proteasome pathway and autophagy-lysosome pathway are two major routes for clearance of aberrant cellular components to maintain protein homeostasis and normal cellular functions. Accumulating evidence shows that these two pathways are impaired during cerebral ischemia, which contributes to ischemic-induced neuronal necrosis and apoptosis. This review aims to critically discuss current knowledge and controversies on these two pathways in response to cerebral ischemic stress. We also discuss molecular mechanisms underlying the impairments of these protein degradation pathways and how such impairments lead to neuronal damage after cerebral ischemia. Further, we review the recent advance on the understanding of the involvement of these two pathways in the pathological process during many therapeutic approaches against cerebral ischemia. Despite recent advances, the exact role and molecular mechanisms of these two pathways following cerebral ischemia are complex and not completely understood, of which better understanding will provide avenues to develop novel therapeutic strategies for ischemic stroke.